User Interface and User Experience Design of Sales Application Mobile Using User Method Centered Design On CV. MK Sejahtera - Restu Djunaedi, Rifqi; Defriani, Meriska; Rafi Muttaqien, Muhammad (RISTEC : Research in Information Systems and Technology, 2022)
Applications are software that are often found in everyday life in this digital era, especially mobile-based applications because mobile devices are almost owned and accessed by various groups at any time. The thing that needs to be considered in a mobile application is the appearance of the user interface or interface because it becomes a bridge between the user and the system used. The design of this interface is designed using the user centered design method in which there are 4 steps in the stages, namely specify the context of use, specify user and organizational requirements, produce design solutions and evaluate design. This application prototype design was designed using the figma application with features such as chat, item search, favorites, order tracking and baskets, as well as for testing 30 respondents using the use questionnaire method with calculations using a Likert scale. with the results of the usability value reaching 82.7%, it shows that the MK Mobile application is very suitable for use by customers to be used as a means of transactions on CV MK Sejahtera.